The Section 504 Process in Middle School: Perspectives of Parents, Teachers and Section 504 Coordinators - Chiasson, Kari; Olson, Myrna R. (Journal of the American Academy of Special Education Professionals, 2007)
This phenomenological study investigated the perceptions of three teachers, four parents, and three Section 504 coordinators regarding the development and implementation of the Section 504 process for children in middle schools who have attention deficit disorder, attention deficit hyperactive disorder, or central auditory processing disorder. Analysis of the data gathered revealed that parents and teachers lacked a clear understanding the Section 504 process and often felt frustrated during the development, implementation, or review of a student’s Individual Accommodation Plan (IAP). Furthermore, lack of time within a teacher’s schedule was a major barrier to collaboration and communication with parents. Based on the findings of this study, the authors make specific recommendations to educators and parents for improving the Section 504 process so that students will receive the greatest benefit.